Penerapan Metode MOORA dan MOOSRA dalam Penentuan Kelayakan Nasabah Penerima Kredit - Mawan Br Hutahaean; Rima Tamara Aldisa; Sardima Siregar; Arina Mana Sikana; Mesran (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
This study aims to determine the eligibility of customers receiving credit. The credit system is needed among the general public. For example for people who want to buy an item but are constrained by costs. So the existence of this credit system is very helpful to the community. However, in the process of granting credit to customers, many problems were found, including problems with customers who later defaulted on credit payments (loans that were not repaid). Therefore Based on this problem, we need a decision support system that helps identify the wrong recipient. The method used in this study is the MOORA method and the MOOSRA method, which is a method for determining priorities for credit recipients, which later by processing the MOORA and MOOSRA methods can help solve problems that occur. A decision support system is a computer-based system composed of interacting components: a language system component, a knowledge system component, and a problem solving system component, and uses data and decision-making models to create a semi-structured It solves structured problems and semi-structured problems and help in decision making. Based on the research that has been done by testing the MOORA and MOOSRA methods, the highest ranking results are those who are entitled to receive credit, namely Alternative 2 named Mujiani with a result of 0.4591 using the MOORA method and similarly using the MOOSRA method, which is the highest ranking also obtained by alternative 2 with a result of 33.2729